PREVALENCE, SURGICAL MANAGEMENT, AND OUTCOME OF PERFORATION OF THE GASTER ASSOCIATED WITH LONG TERM CORTICOSTEROID USE : A COMPREHENSIVE SYSTEMATIC REVIEW - Marito, Yosefina Raju; Brianto, Yohanes Deni (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: In the general population, gastroduodenal perforation can occur as a complication of pre-existing peptic ulcer disease (PUD). In this scenario, the morbidity and mortality are already well documented. The lifetime risk of perforation is approximately 2–10 in cases of untreated PUD, and despite an improvement in resuscitation, and intensive and surgical care, the mortality rate remains around 25. The aim: The aim of this study to show about prevalence, surgical management, and outcome of perforation of the gaster associated with long term corticosteroid use. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 28 articles, whereas the results of our search on SagePub get 9 articles, on Google Scholar 1680 articles. Records remove before screening are 759, so we get 958 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The location of ulcers within the stomach affects the surgical procedure. They may appear with a smaller sac abscess, commonly linked with peritonitis or retroperitoneal abscess. Gastric perforation is a serious and fatal disorder, especially in those who are underweight. Early diagnosis, basic care, primary management, stabilization, nutrient diet, and surgical exploration are all part of initial management.